SOIL TREATMENT AND EFFICIENCY OF HERBICIDES APPLICATION FOR RED BEET CULTIVATION ON THE LIGHT CHESTNUT SOIL OF THE VOLGOGRAD REGION - V. M. Zhidkov; A. V. Khripchenko (Овощи России, 2015)
The optimal combination of soil treatment and herbicides application in condition of the light chestnut soils of the Volgograd region is suggested.